Gamma Knife radiosurgery for brain metastases from gastrointestinal primary. Issue 4 (31st January 2017) - Page, Brandi R; Wang, Edina C; White, Lance; McTyre, Emory; Peiffer, Ann; Alistar, Angela; Mu, Frank; Loganathan, Amritraj; Bourland, John Daniel; Laxton, Adrian W; Tatter, Stephen B; Chan, Michael D
Abstract: Introduction: In this study, we assessed clinical outcomes of patients with brain metastases from a gastrointestinal (GI) primary cancer and patterns of failure after stereotactic radiosurgery including failure within the radiosurgical volume, distant failure and leptomeningeal failure (LMF). We also assessed other factors associated with the patients' neurologic and extraneuraxial disease that may affect clinical outcomes. Methods: We reviewed our institutional series of 62 consecutive patients with brain metastases treated with stereotactic radiosurgery, which included 17 patients with oesophageal, 44 patients with colorectal and one patient with anal canal primary. The median marginal dose to the radiosurgery volume was 17 Gy (range 10–24 Gy). Thirteen patients were treated with whole‐brain radiotherapy (WBRT) prior to GKS. Results: The median dose delivered to the margin of the tumour was 17 Gy (range: 10–24 Gy). The median largest tumour diameter was 2.7 cm (range: 0.60–6.1 cm). The median overall survival (OS) was 7.1 months with a median follow‐up of 6.1 months and a range of 0–31.7 months. Freedom from local failure was 86.5% and 62.2% at 6 and 12 months respectively. Freedom from distant failure was 73.2% and 42.2% at 6 and 12 months, respectively, and 40% of patients died of neurologic death. LMF occurred in seven patients, all of whom had colorectal primaries. Multivariate analysis revealed that craniotomy for resection of brain metastasis (HR = 2.63, P < 0.02), an absence of extracranial disease (HR = 2.28, P < 0.03), and prolonged time to distant brain failure (HR = 2.85, P < 0.01) predicted for improved survival. Conclusions: Colorectal cancer metastases tend to have a higher rate of leptomeningeal failure than other types of GI cancer metastases. Radiosurgical management of brain metastases from GI primary represents an acceptable management option. Neurologic death remains problematic.